The making of aluminium - Russell, Geoff; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 1993)
This program looks at the chemical and electrolytic processes involved in producing aluminium metal. It shows the Portland aluminium smelter in Victoria, in action. In the advanced version, five additional minutes of detailed graphics show the chemistry involved in the production process
Title from title screen
Executive producer, Neil Barrett ; computer graphics/animation/editor, Peter Wiseman
DVD format
Keywords: Aluminum; Aluminum alloys